Utilization of green algae Caulerpa racemosa as feed ingredient for tiger shrimp Penaeus monodon - Widya Puspitasari; Dedi Jusadi; Mia Setiawati; Julie Ekasari; Abidin Nur; Iwan Sumantri (Jurnal Akuakultur Indonesia)
ABSTRACT